Analysis of Acceptance of E-Wallet Technology using UTAUT 2 - Haryo Putro Ramiaji; Ridwan Sanjaya (Soegijapranata Catholic University, 2024)
The Unified Theory of Acceptance and Use of Technology (UTAUT), which explains a person's interest in utilizing information technology and subsequent user behavior, is commonly employed when a new technology is introduced, regardless of whether people can embrace it. UTAUT is an evolution of the Technology Acceptance Model (TAM). One new technology that needs to be evaluated and is widely used in today's society is the ewallet or electronic wallet. Many payment transactions currently use e-wallet technology either directly to stores or buying and selling online. Of course, e-wallet usage cannot be separated from internet use. In Indonesia, the largest internet users are the millennial generation. This study aims to identify the ewallet technology acceptance characteristics that influence reuse among the millennial age by reviewing academic publications that examine the application of UTAUT. Because e-wallet technology influences reuse in the millennial age, this analysis concludes that there is a chance to develop and deploy UTAUT for its acceptability.